(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the actual consumption of hospital meals, and patient satisfaction during inpatient care. Methods: A cross-sectional study was conducted among hospitalized patients receiving hospital meals. Meals were provided in a standardized manner, with an average energy provision of approximately 2000 kcal/day. Data on patient characteristics, meal consumption, and satisfaction were collected and analyzed using descriptive and comparative statistical methods.. Results: Although most patients reported satisfaction with hospital meals across multiple aspects (66.8–76.8%), only 51.4% consumed at least 75% of the provided meals. Nearly half of the patients (48.6%) consumed less than three-quarters of their meals, and 31.3% reported feeling hungry and requiring additional food outside the hospital-provided meals. Satisfaction levels differed significantly across sex, age groups, patient categories, and disease groups (p < 0.05). Conclusions: Despite relatively high patient satisfaction, actual food intake among hospitalized patients remains suboptimal and may not adequately meet individual nutritional needs. Monitoring food intake, enhancing nutrition counseling, and implementing appropriate nutritional support strategies are necessary to improve the effectiveness of inpatient nutritional care.